Does 18F-FDG PET/CT add value to conventional imaging in clinical assessment of chronic disseminated candidiasis? - Rammaert, Blandine; Maunoury, Christophe; Rabeony, Tioka; Correas, Jean-Michel; Elie, Caroline; Alfandari, Serge; Berger, Pierre; Rubio, Marie-Thérèse; Braun, Thorsten; Bakouboula, Prissile; Candon, Sophie; Montravers, Françoise; et al. (Frontiers in Medicine, 2022)
Background. Chronic disseminated candidiasis (CDC) classically occurs after profound and prolonged neutropenia. The aim of the CANHPARI study was to assess the clinical value of adding 18F-fluorodeoxyglucose PET/CT to conventional radiology for initial and subsequent evaluations of CDC. Methods. A pilot prospective study was conducted in 23 French onco-hematological centers from 2013 to 2017 (NCT01916057). Patients ≥18 y.o. suspected for CDC on abdominal conventional imaging (CT or MRI) were included. PET/CT and conventional imaging were performed at baseline and month 3 (M3). Follow-up was assessed until M12. The primary outcome measure was the global response at M3, i.e; apyrexia and complete response to PET/CT. The secondary outcome measure consists in comparison between responses to PET/CT and conventional imaging at diagnosis and M3. Results. Among 52 included patients, 44 were evaluable (20 probable and 24 possible CDC); 86% had acute leukemia, 55% were male (median age 47 years). At diagnosis, 34% had fever and conventional imaging was always abnormal with microabscesses on liver and spleen in 66%, liver in 25%, spleen in 9%. Baseline PET/CT showed metabolic uptake on liver and/or spleen in 84% but did not match with lesion localizations on conventional imaging in 32%. M3 PET/CT showed no metabolic uptake in 13 (34%) patients, 11 still having pathological conventional imaging. Global response at M3 was observed in 8 patients. Conclusion. Baseline PET/CT does not replace conventional imaging for initial staging of CDC lesions but should be performed after three months of antifungal therapy.